RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN PENGADUAN SARANA DAN PRASARANA BERBASIS WEB : Studi Kasus Universitas Pembangunan Nasional Veteran Jakarta - Brian Luhur Prandawa (2020)
Complaints for facilities and infrastructure within the University of National Development Veteran Jakarta by the academic community are currently submitted directly to the General and Financial Subdivisions of each faculty. Next, the complaint was forwarded to the Facilities and Infrastructure Section of the General and Financial Bureau, which is a provider of facilities and infrastructure services at the University of National Development Veteran Jakarta. In addition, the complaints process is still in the form of correspondence so that it is not sufficient to accommodate all complaints quickly and accurately. The purpose and result of this study is to create a web-based complaints management application that can facilitate the academics as well as the Public and Financial Bureau of the University of National Development Veteran Jakarta to submit complaints about facilities and infrastructure and manage and oversee the quality of facilities and infrastructure used by all academics at the University of National Development Veteran Jakarta. The design method created using rapid application development. While the data collection techniques in this research are interviews and observations. As for what is used for testing this sistem later is the Blackbox Testing method.